(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Automobile emits 26% of global CO2 and is among the select sectors whose pollution are continually rising. Cars, road commerce, and aircraft are the three primary sources of greenhouses gas pollutants from the communication industry, and this research focusses on ways to reduce pollutants from these three key categories. A review of emerging technology, such as alternate transportation fuels. It is suggested that technical innovation be used to remove the reliance on petroleum, but it seems that this is unlikely to be the only solution the issue of climate change To attain a stable level of greenhouse gas emissions from transportation, people must alter their habits. It will also be necessary to have a policy. Policymakers are under increasing pressure to address climate change in order to provide sustainable transportation. Although there is a tendency to concentrate on long-term technical solutions, short-term behavioural modification is critical if long-term technological solutions are to be implemented. The advantages of modern technology must be properly appreciated.